Landslide Susceptibility Analysis of Jugal Rural Municipality, Sindhupalchok - Pradhan, Prateek; Dahal, Bhim Kumar (Journal of Science and Engineering, 2023)
Hilly and mountainous areas of Nepal, with challenging terrain, young geology, and heavy monsoon rainfall, are susceptible to landslides and slope instability. To analyze and prepare landslide susceptibility maps, this study selects a typical hilly area, the Jugal Rural Municipality in Sindhupalchok district. Twelve factors contributing to landslides were considered, including slope, aspect, elevation, geology, land use, proximity to roads and drainage, plan curvature, profile curvature, NDVI (Normalized Difference Vegetation Index), soil type and rainfall. Moreover, 286 landslides were identified using high-resolution satellite imagery and field verification as the landslide inventory. These landslides were then randomly divided into two sets: 70% for training and 30% for validation. Bivariate statistical analysis was performed using factor maps and the landslide inventory map. Notably, the analysis revealed a Prediction Rate (PR) of 9.35 for 'Land use', the highest among all factors considered. Since land use is a dynamic factor, we recommend conducting an analysis of land use changes and their impact on landslide susceptibility. Such an assessment would be invaluable during the planning and execution phases of development projects in Nepal's disaster-prone regions.